High interpatient variability of treosulfan exposure is associated with early toxicity in paediatric HSCT: a prospective multicentre study. (19th October 2017) - van der Stoep, M. Y. Eileen C.; Bertaina, Alice; ten Brink, Marloes H.; Bredius, Robbert G.; Smiers, Frans J.; Wanders, Dominique C. M.; Moes, Dirk Jan A.R.; Locatelli, Franco; Guchelaar, Henk‐Jan; Zwaveling, Juliëtte; Lankester, Arjan C.
Summary: Treosulfan‐based conditioning is increasingly employed in paediatric haematopoietic stem cell transplantation (HSCT). Data on treosulfan pharmacokinetics in children are scarce, and the relationship between treosulfan exposure, toxicity and clinical outcome is unresolved. In this multicentre prospective observational study, we studied treosulfan pharmacokinetics and the drug's relationship with regimen‐related toxicity and early clinical outcome in 77 paediatric patients. Treosulfan dose was 30 g/m 2, administered over 3 consecutive days in infants <1 year old ( n  = 12) and 42 g/m 2 in children ≥1 year old ( n  = 65). Mean day 1 treosulfan exposure was 1744 ± 795 mg*h/l (10 g/m 2 ) and 1561 ± 511 mg*h/l (14 g/m 2 ), with an inter‐individual variability of 56 and 33% in the respective groups. High treosulfan exposure (>1650 mg*h/l) was associated with an increased risk of mucosal [Odds ratio (OR) 4·40; 95% confidence interval (CI) 1·19–16·28, P  =   0·026] and skin toxicity (OR 4·51; 95% CI 1·07–18·93, P  =   0·040). No correlation was found between treosulfan exposure and the early clinical outcome parameters: engraftment, acute graft‐versus‐host disease and donor chimerism. Our study provides the first evidence in a large cohort of paediatric patients of high variability in treosulfan pharmacokinetics and an association between treosulfan exposure and early toxicity. Ongoing studies will reveal whether treosulfan exposure is related to long‐term disease‐specific outcome and late treatment‐related toxicity.